A double-network polysaccharide-based composite hydrogel for skin wound healing. (1st June 2021) - He, Yuxin; Li, Yang; Sun, Yadong; Zhao, Shijia; Feng, Miao; Xu, Guoming; Zhu, Haofang; Ji, Peihong; Mao, Hongli; He, Yiyan; Gu, Zhongwei
Graphical abstract: Highlights: A double-network polysaccharide-based composite hydrogel was developed. Mechanical properties of the hydrogel were enhanced by grafted methacrylate groups. The hydrogel functionalized with collagen peptide promoted cell proliferation and wound healing. Abstract: Effective wound dressings are of great significance in preventing infections and promoting wound healing. However, most existing hydrogel dressings have an inadequacy in either mechanical performance, biological activities, or versatilities. Here we presented a double-network cross-linked polysaccharide-based hydrogel composed of collagen peptide-functionalized carboxymethyl chitosan (CS) and oxidized methacrylate sodium alginate (SA). The hydrogel possessed interconnected porous morphologies, suitable swelling ratios, excellent mechanical properties, and favorable biocompatibility. Meanwhile, the in vivo studies using a mouse full-thickness skin defect model showed that the double-network CS/SA hydrogel significantly accelerated wound healing by regulating the inflammatory process, promoting collagen deposition, and improving vascularization. Therefore, the functionalized double-network hydrogel should be a potential candidate as wound dressings